HOW TO ERADICATE HEPATITIS C FROM PAKISTAN? - Farooqi, Javed Iqbal (Journal of Postgraduate Medical Institute, 2017)
Hepatitis C virus (HCV) was identified as a cause of Non-A, Non-B (NANB) hepatitis in 19891,2. Hepatitis C virus belongs to the hepacivirus genus within the laviviridae family. It is an enveloped single stranded positive sense, 9.6 kb and about 50 nm in diameter RNA virus. It is a bloodborn virus and the most common sources include unsafe injection practices, blood transfusion, unsterilized or inadequately sterilized medical equipment and vertical transmission from mother to child and the sexual contact. Hepatitis C virus has 6 major genotypes with variable global distribution: genotypes 1 is mostly found in USA and Europe, genotype 3 mostly in Southeast Asia, genotype 4 mostly in Middle East, Egypt and Central Africa and genotype 5 almost exclusively in South Africa.